Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Konsumen Pada Rumiko Cafe Di Kabupaten Tangerang - Muhamad Alfarizi; Asep Sulaeman (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to determine the effect of Service Quality and Price on Customer Satisfaction at Rumiko Cafe in Tangerang Regency, both partially and simultaneously. The research method used is an associative quantitative method. The population in this study consists of Rumiko Cafe customers, with a total of 99 respondents selected using purposive sampling. Primary data were collected through questionnaires and processed using SPSS Version 25. The tests conducted include validity test, reliability test, classical assumption test, simple and multiple linear regression tests, correlation coefficient test, coefficient of determination test, and hypothesis tests (t-test and F-test). The results show that Service Quality and Price have a positive and significant effect on Customer Satisfaction, both partially and simultaneously. The multiple regression equation obtained is Y = 4.315 + 0.494X1 + 0.324X2. The correlation coefficient (r) value of 0.866 indicates a very strong relationship between the independent variables and the dependent variable. The coefficient of determination (R²) value of 0.751 indicates that 75.1% of the variation in Customer Satisfaction can be explained by Service Quality and Price, while the remaining 24.9% is influenced by other variables not included in this research model. Based on the simultaneous test, the calculated F value is greater than the table F value (144.482 > 3.09) with a significance value below 0.05, indicating that Service Quality and Price have a positive and significant simultaneous effect on Customer Satisfaction at Rumiko Cafe in Tangerang Regency. Keywords: Service Quality; Price; Customer Satisfaction.